Communication Patterns of The Persis Solo Boys 1923 Group Supporter Community (Qualitative Descriptive Study) - Hasyin, Fadhli; Sanjaya, Andika (Jogjakarta Communication Conference (JCC), 2025)
Persis Solo is an Indonesian Liga 1 football club owned by Kaesang Pangarep, the son of Indonesia’s seventh former president, Joko Widodo. Persis Solo has various supporter groups, one of which is Boys 1923. Boys 1923 is a supporter community that occupies the east stand, gate 8, of Manahan Stadium in Solo. This group embraces a casual ideology and holds the vision and mission of